A scoping review of the research on school absences and return to school - Laurén-Knuutila, Tiina-Reetta; Salminen, Jaanet; Junttila, Niina; Alanko, Katarina (Routledge, Taylor & Francis Group, 2026)
Prolonged school absence is linked to serious individual and societal consequences, including psychological distress and increased dropout risk, making effective reintegration strategies essential. This review synthesizes 45 years of research on school re‑engagement through Bronfenbrenner’s bioecological model. A search across nine databases identified 67 eligible studies involving students aged 6–18 from high‑income countries. Descriptive analysis examined publication trends, disciplines, methods, informants, and types of school attendance problems (SAPs). Research was dominated by psychology and concentrated in Europe, the United States, and Australia. Most studies focused on emotionally based school avoidance, often using case or intervention designs, with cognitive-behavioral therapy as the dominant approach. Interventions primarily targeted micro- and mesosystem levels, with limited attention to broader systemic factors. This imbalance risks reinforcing individualised explanations and constraining sustainable solutions. Future research should emphasize systemic, family-, and community-level approaches to support long-term school re-engagement and resilience.